Nicotinamide treatment reduces the levels of oxidative stress, apoptosis, and PARP-1 activity in Aβ(1–42)-induced rat model of Alzheimer's disease. (February 2014) - Turunc Bayrakdar, E.; Uyanikgil, Y.; Kanit, L.; Koylu, E.; Yalcin, A.
Abstract: The underlying mechanisms of Alzheimer's Disease (AD) are still unclear. It is suggested that poly(ADP-ribose) polymerase-1 (PARP-1) overactivation can cause neuroinflammation and cell death. In this study we searched the effects of nicotinamide (NA), endogenous PARP-1 inhibitor, on oxidative stress, apoptosis, and the regulation of PARP-1 and nuclear factor kappa B (NF-κB) in amyloid beta peptide (1–42) (Aβ(1–42))-induced neurodegeneration. Sprague–Dawley rats were divided into four groups as control, Aβ(1–42), Aβ(1–42) + NA(100 and 500 mg/kg). All groups were stereotaxically injected bilaterally into the hippocampus with Aβ(1–42) or saline. After surgery NA administrations were made intraperitoneally (ip) for 7 days. In order to investigate the effects of Aβ(1–42) and NA, protein carbonyls, lipid peroxidation, reactive oxygen species (ROS) production, glutathione (GSH) levels, activities of antioxidant enzymes (catalase, superoxide dismutase, glutathione peroxidase), mitochondrial function, mRNA and protein levels of PARP-1, NF-κB, p53, Bax, and Bcl-2 were measured in specific brain regions such as cortex and hippocampus. Aβ(1–42) treatment only increased the oxidative stress parameters and caused decline in antioxidant enzyme activities, mitochondrial function, and GSH levels. Also, overexpression of PARP-1, NF-κB, p53, Bax, and the decreased levels of Bcl-2 were observed in Aβ(1–42)-treated group. NA treatments against Aβ(1–42)-upregulated Bcl-2 and downregulated PARP-1, NF-κB, p53, and Bax levels. NA treatments also decreased the oxidative stress parameters and elevated antioxidant enzyme activities, GSH levels, and mitochondrial function against Aβ(1–42) treatment. These data suggest that NA may have a therapeutic potential in neurodegenerative processes due to the decreased levels of oxidative stress, apoptosis, and PARP-1 activity.